A Synthetic Proposal about the Corinthian Resurrection Deniers - Harriman, K. R. (Novum Testamentum, 2020)
Most standard analyses of the identification of the deniers of the resurrection and the nature of their denial in 1 Cor 15:12 evaluate three sets of options: denial of any post-mortem fate, over-realized eschatology, or dualistic anthropology from Greco-Roman philosophy. The author argues that all of these theories are inadequate, and proposes a theory that identifies the Corinthian resurrection deniers as a cross-section of members from upper and lower classes, with varying levels of education, whose denial of the general resurrection emerges from a variety of sources in philosophy and the myths of popular religion.